Public Awareness regarding the Differences between Ophthalmologists and Optometrists among Saudi Adults Living in Riyadh: A Quantitative Study - Mohammed Hamad Aldebasi; Nasser Abdalazez Alsobaie; Abdulrahman Yousef Aldayel; Khalid Mousa Alwusaidi; Tariq Alasbali (Journal of Ophthalmology)
Awareness of the patients to the differences between ophthalmologists and optometrists has been recognized as an important factor influencing patient utilization of available eye care services. This study aimed at assessing the public’s knowledge of the differences between ophthalmologists and optometrists among the residents of Riyadh, Saudi Arabia. An online questionnaire was administered to adults in Riyadh, Saudi Arabia, from January to February in 2018. The number of the respondents was 1579. Results show that 50% (n=789) of the participants had fair knowledge of the differences between ophthalmologists and optometrists, while 32% (n=505) had poor knowledge. After multivariate logistic regression analysis, there was a significant association between satisfactory knowledge and visiting an optometrist (odds ratio (OR): 0.75, 95% CI: 0.57–0.98), age older than 26 (OR: 1.73, 95% CI: 1.17–1.19), higher level of education (OR: 1.92, 95% CI: 1.54–2.4), and wearing spectacles (OR: 0.57, 95% CI: 0.45–0.73). Given the low level of public knowledge regarding the differences in the duties between ophthalmologist and optometrists among a Saudi population, there is great potential for general population education through awareness campaign and social media regarding eye care provider’s duties and practices.